(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Oral contraceptive pill (OCP) is widely used by millions of women of various socioeconomic conditions.Use of low dose oestrogen and newer progesterone in OCP now associated with less thromboembolic and cardiovascular risk. The safety aspects of these pills had not been investigated in details in malnourished women of developing countries. In the present study the effects of the pillson coagulation status have been studied. Objective: To explore the effect of the most widely used low dose OCP (Shukhi) on coagulation status of Bangladeshi women with normal and low BMI(Body Mass Index). Materials and Methods: The study population group (n=29) comprised of women with normal BMI and the underweight group (n=11,BMI<18.5). Both groups use low dose OCP(30?g ethinyl estradiol and 150?g levonorgestrel) for 6-60 months. The coagulation status were assessed as follows: Plasma Fibrinogen, Prothrombin time and Platlete aggregation and Anticoagulation statuseg: AntithrombinIII (ATIII). Result:Coagulation status showed no significant difference in platelet aggregation between the groups. Plasma fibrinogen median value (450mg/dl) just exceeded the upper limit of reference range (normal range: 200-400mg/dl) in normal BMI. In contrast, the corresponding value in the low BMI (318mg/ dl) group was almost at the middle of the reference range. A significantly prolonged prothrombin time (13.80 seconds) was found in the low BMI group (p=0.058); values were still within the reference range (10-14 seconds). No significant correlation existed between plasma fibrinogen, prothrombin time and platelet aggregation in normal BMI or low BMI groups. Antithrombin IIIactivity in normal BMI group was 108% and in low BMI group it was 105%. Atendency of positive correlation existed between antithrombin III activity and BMI in low BMI pill users (r=0.591,p=0.072). Conclusion:The study suggested that a) Reported risk of procoagulant or thromboembolic changes in pill users is lower in low BMI &normal BMI and b) Low BMI users showed significantly longer prothrombin time due to the effect of malnutrition itself or due to the effect of pills in this nutritional background. J Bangladesh Coll Phys Surg 2017; 35(1): 3-8